2023
DOI: 10.1038/s41421-022-00517-9
|View full text |Cite
|
Sign up to set email alerts
|

Lyophilized mRNA-lipid nanoparticle vaccines with long-term stability and high antigenicity against SARS-CoV-2

Abstract: Advanced mRNA vaccines play vital roles against SARS-CoV-2. However, most current mRNA delivery platforms need to be stored at −20 °C or −70 °C due to their poor stability, which severely restricts their availability. Herein, we develop a lyophilization technique to prepare SARS-CoV-2 mRNA-lipid nanoparticle vaccines with long-term thermostability. The physiochemical properties and bioactivities of lyophilized vaccines showed no change at 25 °C over 6 months, and the lyophilized SARS-CoV-2 mRNA vaccines could … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…LNPs are known to be fragile and subject to aggregation and breakage when physically stressed, such as during buffer exchange, freeze–thaw cycles, or mechanical stirring. The LNPs in this study have a typical range of polydispersity with PDI below 0.2 (Table ) and comparable or below those reported in the literature for typical LNPs. PDI is expected to be impacted by the presence of aggregates.…”
Section: Resultssupporting
confidence: 66%
“…LNPs are known to be fragile and subject to aggregation and breakage when physically stressed, such as during buffer exchange, freeze–thaw cycles, or mechanical stirring. The LNPs in this study have a typical range of polydispersity with PDI below 0.2 (Table ) and comparable or below those reported in the literature for typical LNPs. PDI is expected to be impacted by the presence of aggregates.…”
Section: Resultssupporting
confidence: 66%
“…After that, the vaccine exhibited a significant decrease in mRNA integrity and particle size, as well as a decrease in immunogenicity and mRNA concentration [ 109 ]. Recently, a study reported that the physiochemical properties and bioactivities of lyophilized vaccines showed no change at 25 °C over 6 months, and the lyophilized SARS-CoV-2 mRNA vaccines could elicit potent humoral and cellular immunity whether in mice, rabbits, or rhesus macaques [ 110 ].…”
Section: Factors Affecting Mrna Vaccine Stabilitymentioning
confidence: 99%
“…Besides, lyophilization of mRNA‐LNP platforms can retain the stability and high antigenicity of mRNA at 25 °C over six months, thus dramatically improving the accessibility of mRNA‐based therapeutics in remote areas. [ 233 ] Apart from LNP, Badieyan et al. used collagen matrix to deliver mRNA and this platform remained stable for at least six months at room temperature.…”
Section: Summary and Perspectivementioning
confidence: 99%